DIDIKAN SUBUH PADA MADRASAH DINIYAH TAKMILIYAH AWALIYAH (MDTA) AS-SALAM DI PEKANBARU - Nur Hidayah; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research about " Dawn Education of the As-Salam Madrasah Diniyah Takmiliyah Awaliyah (MDTA) in Pekanbaru." Formulation of the problem that how the dissemination of religious values through education of the dawn of Madrasah Diniyah Takmiliyah Awaliyah (MDTA) As-Salam in Pekanbaru? How the influence of religious values in the activity patterns of children behaviour in Madrasah Diniyah Takmiliyah Awaliyah (MDTA) As-Salam in Pekanbaru? This research aims to explain about how the process of socialization and the effect on the child's behavior, students after graduating from MDTA As-Salam. The research used Qualitative methods. The subject in this study is as much as eight children. There are some techniques of Data collection that document, observation and interview. The result of this research shows that there is no problems of process of socialization in MDTA As-Salam, everything went smoothly and easily. But, only the problem of the children in the study, and the effect on what brings the child against the behaviour, be it in terms of implementing the prayers, the Qur’an, as well as akhlaq, memorizing prayers/surah read taught. Whether it was all digested and aplicated? or only practiced just in school surroundings while out of school is no longer in practise. In accordance with the theory of socialization, religion, and values that can affect the child's behavior.Keywords: Socialization, MDTA, Dawn Education, Behavior, Children